2012
DOI: 10.1002/mrd.22125
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ABCB1 and ABCC1 transporters in sea urchin Echinometra lucunter fertilization

Abstract: Fertilization is an ordered sequence of cellular interactions that promotes gamete fusion to form a new individual. Since the pioneering work of Oskar Hertwig conducted on sea urchins, echinoderms have contributed to the understanding of cellular and molecular aspects of the fertilization processes. Studies on sea urchin spermatozoa reported the involvement of a plasma membrane protein that belongs to the ABC proteins superfamily in the acrosome reaction. ABC transporters are expressed in membranes of eukaryot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…CCNA1 is an important cell cycle regulator that plays an important regulatory role in germ cell meiosis, indicating that it plays an important role in animal reproduction [29,30,31,55]. ABCC1 is associated with the transport of several compounds or ions across biomembranes and is crucial for successful fertilization [56]. However, few studies have investigated the effect of the SLC5A1 , CCNA1 , and ABCC1 genes on litter size in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…CCNA1 is an important cell cycle regulator that plays an important regulatory role in germ cell meiosis, indicating that it plays an important role in animal reproduction [29,30,31,55]. ABCC1 is associated with the transport of several compounds or ions across biomembranes and is crucial for successful fertilization [56]. However, few studies have investigated the effect of the SLC5A1 , CCNA1 , and ABCC1 genes on litter size in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent results can be attributed to calcein self‐quenching, which may be related to several reasons since the presence of ABC transporters activity (Silva‐Neta et al, ) to the small cell size or the small amount of cytoplasm compared to the large mitochondrion in the spermatozoa. Calcein‐AM is an ABC transporters substrate and CsA blocks the activity of several ABC proteins, which increases calcein concentration inside the cell (Hait et al, ; Tiberghien and Loor, ; Marques‐Santos et al, ; Hamdoun et al, ; De Souza et al, ; Silva‐Neta et al, ). Additionally, Hamann et al () demonstrated that calcein exhibits a strong self‐quenching that is responsible for the reduction in the fluorescence level according to the cell size.…”
Section: Discussionmentioning
confidence: 99%
“…The mapping of the sea urchin S. purpuratus genome revealed 65 genes encoding ABC transporters (Sodergren et al, ). Recently, our group characterized the activity of ABCB1 and ABCC1 proteins in the gametes, embryonic cells, and pluteus larvae of Echinometra lucunter , a widespread sea urchin that inhabits the tropical and temperate waters of the Atlantic Ocean (De Souza et al, ; Silva‐Neta et al, ; Torrezan et al, ). Our data suggest that ABC transporters act as a biochemical barrier that confers protection against chemical stress in E. lucunter embryos, but are also crucial to the fertilization process.…”
Section: Introductionmentioning
confidence: 99%